Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasaan Tamu Pada Kegiatan Mice Di Pangeran Beach Hotel Padang - Jannah, Riza Bill; Suyuthie, Hijriyantomi (CV. ITTC INDONESIA, 2024)
The purpose of the research conducted is to find out how guest satisfaction following MICE activities at Pangeran Beach Hotel Padang is influenced by the quality of services and facilities offered. This analysis uses a causal associative approach with descriptive quantitative. Data collection is done through indirect communication by distributing questionnaires through Google Forms with a Likert scale to participants of MICE activities. Furthermore, the data were processed using the SPSS program. This research involved people who had participated in MICE activities at Pangeran Beach Hotel Padang from January to June 2024. The sample numbered 130 people, and all participants were at least 18 years old. This research shows that the quality of service including good level is 4.03, facilities in good category is 4.13, and guest satisfaction in good category is 4.15%. With a calculated F value of 129.962 and an R square of 0.672, it was found that variable X had a significant influence on variable Y of 67.2%. For the service variable, the quality of the regression coefficient is found to be 0.525 with the acquisition of 0.000-0.05, which means that each increase in service will increase guest satisfaction by 0.525 units of satisfaction. For the facility variable, a regression coefficient value of 0.561 was found with a gain of 0.0